Analisis SWOT PT. Pusat Gadai Indonesia - Wulandari, Gita Mei; ., Daspar (CV. ITTC INDONESIA, 2025)
This study aims to analyze the internal and external conditions of PT Pusat Gadai Indonesia using a SWOT analysis approach (Strengths, Weaknesses, Opportunities, Threats) as part of a Mid-Semester Examination assignment for the Strategic Management course. The analysis reveals that PT Pusat Gadai Indonesia possesses several strengths, including a strong reputation, fast pawn processes, competitive interest rates, as well as technological support and responsive customer service. However, the company also faces significant weaknesses such as lack of product innovation, limited market reach beyond Java, and suboptimal digitalization. Externally, the company has considerable opportunities due to increasing public demand for quick funding, the growth of MSMEs, and potential partnerships with fintech companies. External threats include intense competition from Pegadaian and fintech lenders, regulatory changes, and economic fluctuations. Based on the EFE Matrix, the company scores 2.65, indicating a fairly good ability to respond to external dynamics. The recommended SWOT strategies include developing a mobile application, enhancing digital promotion, forming fintech partnerships, and strengthening risk management. The findings suggest that PT Pusat Gadai Indonesia should prioritize digital transformation and market expansion to remain competitive in an increasingly dynamic industry landscape.